Efeitos da desnervação renal na hipertensão espontânea experimental: repercussões sobre a aorta e sobre o sistema nervoso autônomo - Moreira, Nathalia Juocys Dias [UNIFESP] (2016)
The procedure of renal denervation (RDN) has been proposed as an innovative treatment in patients with resistant hypertension because this procedure leads to a decrease in renal vascular resistance, reduce renin secretion and increase renal excretion of water and sodium. However, the mechanisms involving the changes of low arterial pressure in acute response are not yet fully understood. This way, we study the autonomic control of circulation in SHR rats (spontaneous hypertensive rats), before and after RDN as well as hydric balance and the aorta contractile function. We used Wistar and SHR male rats divided in four experimental groups: Normotensive group sham (NS) composed of 7 wistar rats submitted to sham surgery; Desnervated normotensive group (ND) composed for 10 wistar rats submitted to RDN; SHR sham group (SS) composed for 6 SHR rats submitted to sham surgery; Desnervated SHR group (SD) composed for 8 SHR rats submitted to RDN. 24 to 48 hours after intervention (RDN or sham), the hemodynamic parameters were measured and the data stored for further analysis of blood pressure, heart rate and autonomic variables. The animals were housed in metabolic cages before and 24 hours after RDN to evaluate water balance. At the end of the protocol (7 to 10 days), the animals were euthanized for removal of the aorta for functional or histological analysis. The mean blood pressure of the denervated SHR group showed significant decrease 24 to 48 hours after RDN (167±4,64 mmHg pre vs 139±4,78 mmHg post). Although no statistical significance was observed, the denervated hypertensive animals experienced increased bradycardic response ah the time after intervention (0,73±0,09 pre vs 1,08±0,11 bpm/mmHg post). It was also observed an important increase in urinary volume after RDN in these animals (15±1,19 mL pre vs 29±5,98 mL post). In addition, renal sympathetic nerve removal was able to improve the contractile response to phenylephrine in both normortensive and hypertensive animals. Considering that hypertensive animals (SHR) have increased tonic activity of the sympathetic nervous system for different regions, renal denervation in these animals can modify the autonomic modulation on heart and vessels. This modification is probably associated with the fall in BP, wich also appears to have contributed to increase urinary volume and changes in the contractile function of the descending aorta in these animals.